-2(x-2)=6x-28

Simple and best practice solution for -2(x-2)=6x-28 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x-2)=6x-28 equation:



-2(x-2)=6x-28
We move all terms to the left:
-2(x-2)-(6x-28)=0
We multiply parentheses
-2x-(6x-28)+4=0
We get rid of parentheses
-2x-6x+28+4=0
We add all the numbers together, and all the variables
-8x+32=0
We move all terms containing x to the left, all other terms to the right
-8x=-32
x=-32/-8
x=+4

See similar equations:

| 23=x2 | | 2.2(2x+2)=2x3.5 | | -60+12b=−60+12b=-48−48 | | n+3/4=9/10 | | 15-p=9+0.5p | | 6=-3x+36x= | | x^2+120x-4|500=0 | | 10p-50=5000 | | -3(5a+6)=2(3a+8) | | Z3=8i | | -(5x-3)=3x+2 | | s*6+40=184 | | 8p-16=56 | | 6(x+2)-7x=-14 | | 2.20g=53.90 | | 7^(x-3)+7^(x-2)+7^(x-1)=57 | | 5x+52+6x=25 | | -0=x+5 | | 2x=100x= | | x-20+2x=25 | | 125^3x+7=25^5x−11 | | (10)^2x+1=3 | | -7g−8=-8g | | s/4+4=15 | | 5(g=8)-7=103 | | 9t+20=7t-12 | | 24,000-4000/3x=4000 | | 4w-2+2w=28 | | +22x=53.90 | | 10^2x+1=3 | | 15s-20=375 | | 3x=2x+503x=2x+50 |

Equations solver categories